The dark room ebook - Duggan, Gerry (The Dark Room., 2022)
The hunt for a camera containing an undeveloped photo of the face of true evil threatens to wipe out New York City one chilly autumn evening. Doune Mahoney is the curator of a private collection of extremely dangerous cursed objects, and her night’s about to go to hell. Werewolves, secret societies, blessed animals, cursed objects, and more, in a fantasy horror comedy from X-Men and Deadpool writer GERRY DUGGAN, your new favorite artist SCOTT BUONCRISTIANO, and color artist extraordinaire TAMRA BONVILLAIN. Take a deep dive into THE DARK ROOM, a world the creators will be returning to for many years.